ChemInform Abstract: An Efficient Sequential One‐Pot Base‐Mediated C—O and Pd‐Mediated C—C Bond Formation: Synthesis of Functionalized Cinnamates and Isochromenes. Issue 4 (31st January 2013) - Reddy, A Gopi Krishna; Krishna, J.; Satyanarayana, G.
Abstract The one‐pot synthesis of cinnamates (III) from ortho‐bromobenzyl alcohols and olefins (II) involves sequential oxy‐Michael addition and intramolecular Heck coupling.